2016
DOI: 10.1111/1750-3841.13501
|View full text |Cite
|
Sign up to set email alerts
|

Opinion of Spanish Consumers on Hydrosustainable Pistachios

Abstract: Fruits and vegetables cultivated under controlled deficit irrigation (CDI) are called hydrosustainable (hydroSOS) products and have its own personality and are environmentally-friendly. Focus groups helped in classifying key farming, sensory, and health concepts associated with CDI-grown pistachios. Besides, focus groups also helped in stating that a logo was needed for these special foods, and that a hydroSOS index is also essential to certify that the products have been controlled by a control board. Conjoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 47 publications
4
52
0
1
Order By: Relevance
“…RDI table olives belong to a group of vegetable products named hydroSOStainable . These products are characterized by having unique characteristics: (i) high intensity of some key sensorial attributes, (ii) high content of some nutritional and functional components, and (iii) reduced use of water, which is a benefit for both farmers (economic benefit) and for the environment (water sustainability) …”
Section: Introductionmentioning
confidence: 99%
“…RDI table olives belong to a group of vegetable products named hydroSOStainable . These products are characterized by having unique characteristics: (i) high intensity of some key sensorial attributes, (ii) high content of some nutritional and functional components, and (iii) reduced use of water, which is a benefit for both farmers (economic benefit) and for the environment (water sustainability) …”
Section: Introductionmentioning
confidence: 99%
“…4). Noguera-Artiaga et al (2016) also found that consumers are willing to pay a reasonably higher price for hydroSOS pistachios, if they are properly labeled and identified. However, further research is needed to check whether this greater willingness to pay is the similar for all fruits.…”
Section: Summary Conclusion and Future Research Needsmentioning
confidence: 95%
“…Also, an international consumer study about the opinion of European consumers on pistachios grown under RDI indicated that the kernels resulting from moderate RDI applied during stage II obtained a higher intensities of characteristic sensory attributes and a greater level of satisfaction among international consumers than kernels from FI trees or from those exposed to severe RDI during stage II (Carbonell-Barrachina et al, 2014;Noguera-Artiaga et al, 2016).…”
Section: Pistachio (Pistacia Vera L)mentioning
confidence: 99%
See 1 more Smart Citation
“…Pomegranate shrubs (Punica granatum L., cvs 'Mollar de Elche' and 'Wonderful') were cultivated on a farm located in Murcia (Spain) under regulated deficit irrigation (RDI). [14][15][16][17] Pomegranate cvs 'Mollar de Elche' and 'Wonderful' , figs (Ficus carica, cv. 'Colar'), jujubes (Ziziphus jujube, cv.…”
Section: Plant Materials and Smoothie Preparationmentioning
confidence: 99%